Occupational outlook handbook 2008 - 2009 (McGraw-Hill, 2008)
The Occupational Outlook Handbook has been respected as the job seeker's number-one source of critical decision-making data for more than 50 years. From able seaman to zoologist, the latest edition gives you comprehensive information on more than 250 occupations, encompassing nearly 90 percent of the jobs in the U.S. economy.